2019
DOI: 10.1101/720797
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Haplotype-Resolved Cattle Genomes Provide Insights Into Structural Variation and Adaptation

Abstract: We present high quality, phased genome assemblies representative of taurine and indicine cattle, subspecies that differ markedly in productivity-related traits and environmental adaptation. We report a new haplotype-aware scaffolding and polishing pipeline using contigs generated by the trio binning method to produce haplotype-resolved, chromosomelevel genome assemblies of Angus (taurine) and Brahman (indicine) cattle breeds. These assemblies were used to identify structural and copy number variants that diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Using F-statistics, we found 16 lineage-differential CNV segments between Bos indicus and Bos taurus. Compared to the previous studies [12,16], 8 genes overlapped by the lineage-differential CNVs were novel. However, both of our and previous studies showed similar functions (heat resistance, lipid and ATP metabolic process) for the differential CNV between Bos taurus and Bos indicus [12,16].…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Using F-statistics, we found 16 lineage-differential CNV segments between Bos indicus and Bos taurus. Compared to the previous studies [12,16], 8 genes overlapped by the lineage-differential CNVs were novel. However, both of our and previous studies showed similar functions (heat resistance, lipid and ATP metabolic process) for the differential CNV between Bos taurus and Bos indicus [12,16].…”
Section: Discussionmentioning
confidence: 71%
“…Compared to the previous studies [12,16], 8 genes overlapped by the lineage-differential CNVs were novel. However, both of our and previous studies showed similar functions (heat resistance, lipid and ATP metabolic process) for the differential CNV between Bos taurus and Bos indicus [12,16]. We also found genes for muscle development might be under selection, which would provide genetic evidences for the meat difference between the two cattle subspecies.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations